2021
DOI: 10.1002/anie.202104677
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Generation of Hypervalent Bromine(III) Compounds

Abstract: In sharp contrast to hypervalent iodine(III) compounds, the isoelectronic bromine(III) counterparts have been little studied to date. This knowledge gap is mainly attributed to the difficult-to-control reactivity of l 3 -bromanes as well as to their challenging preparation from the highly toxic and corrosive BrF 3 precursor. In this context, we present a straightforward and scalable approach to chelation-stabilized l 3bromanes by anodic oxidation of parent aryl bromides possessing two coordinating hexafluoro-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 61 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…To better understand the mechanism of bromane formation, we intended to combine detailed electroanalytical studies with quantum chemical modeling. In our previous work, [15] we have already obtained some information about bromoarene oxidation by performing preliminary electroanalytical experiments. Thus, voltammetric analysis of 1 at 10 mV s À 1 between 0 and 2.7 V versus Ag/0.01 M AgNO 3 (E ref = À 87 mV vs. Fc/Fc + couple) [16] using an electrolyte consisting of 0.1 M NBu 4 BF 4 in HFIP showed that each of the bromoarenes exhibits a single irreversible anodic feature.…”
Section: Anodic Bromane Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the mechanism of bromane formation, we intended to combine detailed electroanalytical studies with quantum chemical modeling. In our previous work, [15] we have already obtained some information about bromoarene oxidation by performing preliminary electroanalytical experiments. Thus, voltammetric analysis of 1 at 10 mV s À 1 between 0 and 2.7 V versus Ag/0.01 M AgNO 3 (E ref = À 87 mV vs. Fc/Fc + couple) [16] using an electrolyte consisting of 0.1 M NBu 4 BF 4 in HFIP showed that each of the bromoarenes exhibits a single irreversible anodic feature.…”
Section: Anodic Bromane Generationmentioning
confidence: 99%
“…Inspired by the successful in situ generation of reactive hypervalent iodine species via anodic oxidation of iodoarene precursors, [13,14] we presented a convenient electrochemical approach toward synthesis of 2. [15] The method is based on the anodic oxidation of parent aryl bromides 1 containing two coordinating hexafluoro-2-hydroxy-propanyl substituents under galvanostatic conditions in an undivided cell (Eq. (1) in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the "Martin ligand" is an excellent alternative strategy for the preparation of stable λ 3 -bromane (4; Figure 1B). 10,11 These approaches, however, are less than ideal in terms of versatility. In 1984, Frohn and co-workers revolutionized this field by the synthesis of difluoro-λ 3 -bromane 6 (Frohn's reagent): 12 the use of the substitution reaction of BrF 3 with arylsilanes 5 circumvents the unfavorable oxidation process.…”
mentioning
confidence: 99%
“…They elegantly overcame the energetic impasse by leveraging intramolecular λ 3 -bromane formation with the pyrolysis reaction of the diazonium salt of 2-amino-2′-bromobiphenyl ( 1 ), obtaining cyclic o , o ′-diphenylene-λ 3 -bromane ( 2 ; Figure A). The use of the “Martin ligand” is an excellent alternative strategy for the preparation of stable λ 3 -bromane ( 4 ; Figure B). , These approaches, however, are less than ideal in terms of versatility. In 1984, Frohn and co-workers revolutionized this field by the synthesis of difluoro-λ 3 -bromane 6 (Frohn’s reagent): the use of the substitution reaction of BrF 3 with arylsilanes 5 circumvents the unfavorable oxidation process.…”
mentioning
confidence: 99%
“…wherein the slope provides a measure of the influence of the substituents upon the observed potential, while the intercept refers to the E P/2 of the unsubstituted compound of the series. [29] The stabilization of the characteristic pseudo-trigonal bipyramidal geometry of l 3 -bromanes 3 by 2-benzobromaoxole rings (for X-ray structure of 3 a, see Table 1 graphics) [30] endows Martins bromine(III) species with remarkable stability. Given the high oxidizing power and strong electrophilicity of l 3 -bromanes, [13a] the observed stability is striking.…”
Section: Angewandte Chemiementioning
confidence: 99%